THE USE OF SOCIAL MEDIA AS A SOURCE OF COMPLEMENTARY FEEDING INFORMATION FOR MOTHERS - Hanindita, Meta Herdiana; Widjaja, Nur Aisiyah; Hidayati, Siti Nurul; Irawan, Roedi; Hidayat, Boerhan (The Indonesian Journal of Public Health, 2024)
Introduction: In the digital age, social media (SM) has undeniably transformed the way parents access information, including complementary feeding (CF) practices. Approximately 57.1% mothers in Indonesia obtained information about CF from the internet, ranging from parenting forums to social media platforms like Instagram. Aims: To explore the use of SM as source of CF information among mothers in Indonesia. Method: Exploratory cross-sectional study was conducted in 1631 mothers of children 0-23 months in May 2023, using an online questionnaire. The analysis of the data was conducted using the statistical software SPSS 21.0 Results: Of all the subjects, the largest group consisted of those aged 26-30 years. A majority had a high level of education, had SM, and spent 30-60 minutes (59.2%) searching for CF information. Full-time mothers were more influenced by SM (p=0.043). A notable distinction existed in the choice of social media based on the level of education. The higher the education, the more Instagram was used, while the lower the education, the more TikTok was used (mothers p=0.000; fathers p=0.002). The higher the education, the more information sources were sorted (mothers p=0.014; fathers p=0.000), and the more the educational background of the informant was considered (mothers p=0.000; fathers p=0.000). Conclusion: Mothers seek CF information from SM because it is faster, easier and convenient. However, it is often not evidence-based, and the amount of conflicting information confuses parents. Health efforts with a promotive approach that are evidence-based, understandable and applicable are needed and can be carried out through SM.